ESTIMATE RIG CAPACITY AND RENTAL COST IN DRILLING OPERATION GH-02 WELL EXPLORATION MATALOKO GEOTHERMAL FIELDRATION GH-02 WELL EXPLORATION MATALOKO GEOTHERMAL FIELD (ASEAN Engineering Journal, 2022)
Exploration well GH-02 will be drilled directionally at an inclination of 44º and a target of 5920 ft MD or 4840 ft TVD. So that the drilling process can be safe, the rig capacity must be determined optimally so that it is not over capacity which causes higher rig rental costs and also low capacity which causes disruption of the drilling process. The main components that influence the calculation of the horsepower required by the rig are the hoisting system, the rotary system, and the circulation system. The amount of horsepower required in the hoisting system is influenced by the lifting velocity, the hook load and the efficiency factor. While the rotary system is influenced by the amount of rpm and the target depth. Circulation system is influenced by the pump flow rate and pressure loss along the circulation system. The total horsepower required can be calculated by adding up the horsepower from the hoisting system, rotary system, circulation system, plus the safety factor of 100-250 HP for rigs with more than 1000 horsepower. The drilling time is designed optimally so that not much time is wasted which can cause the drilling costs to increase expensive. The amount of the rig rental cost is obtained from the rig rental cost per day with the planned drilling time. The results of the case study calculations show that the rig capacity is 1500 horsepower, drilling is carried out for 22 days and the cost of renting the rig is 660000 USD